IP-10 as a Non Sputum Biomarker in TB Treatment Monitoring (Majalah Kedokteran Bandung, 2021)
There are currently still limitations in the diagnosis of tuberculosis (TB). Sputum collection as specimen for diagnosis is not only difficult but also has low sensitivity.In blood, IP-10/CXCL-10 chemokine plays a role in inducing the movements of chemotactic inflammatory cells towards the sites of inflammation. A high level of IP-10 is found in active pulmonary TB patients and significantly decline after the patients have completed the TB treatments. The aim of this study was to analyze the decline of the IP-10 level before and after 2 months of TB treatment. This study was conducted from March toJuni 2020. This was a comparative observational cohort study on active pulmonary TB patients who were >18 years old at the DOTS Clinic of Dr. Hasan Sadikin General Hospital Bandung. Thirty patients who met the inclusion criteria were followed up until 2 months of TB treatment. Serum of  these patients were collected and examined for the IP-10 level before and after 2 months of TB treatment. It was demonstrated that the median IP-10 level in new active pulmonary TB patients was 384.1 pg/mL (136.70–779.80) and dropped to 251.85 pg/mL (91.10–698.30) (p
Keywords: IP-10; Tuberculosis; Tuberculosis treatment monitoring.